Oscillation criteria for three dimensional nonlinear conformable fractional delay differential system with forcing terms (2022)
In this paper, we study the oscillation of three dimensional non- linear conformable delay differential system with forcing terms. By using generalized Riccati transformation, conformable derivatives and some inequality based techniques, we obtain several oscillation criteria for the system. Furthermore, an example is given to authenticate our results.